COVALENT IMMOBILIZATION OF SAPINDUS PEROXIDASE ON POLYANILINE - JAGTAR SINGH; ATIN SHARMA (International Journal of Pharma and Bio Sciences, 2013)
Covalent immobilization of peroxidase is convenient in continuous processes to improve them economically. In the present study, peroxidases from Sapindus mukorossi were immobilized and used for removal of 4-chlorophenol (4-CP) by the polymerization pathway. Five milligram of vacuum dried polyaniline-glutaraldehyde composite was incubated in 1ml sodium acetate buffer (50mM;pH 5.0) containing 0.5 mg/ml of peroxidase, at 4°C, and the mixture was maintained under orbital agitation. When free and immobilized peroxidases were tested for their ability to remove 4-CP from aqueous solution, temperature and pH optima for both was recorded at 40°C and 5.0 respectively. Km and Vmax with respect to H2O2 were calculated to be 0.44mM and 134.7 E.U and with respect to guaiacol were determined to be 3.5mM and 70.54 E.U. respectively.The removal of 4-CP was maximum when the immobilized enzymes were incubated in a batch reaction for 90 minutes. The percentage removal of 4-CP (0.2mM solution) was reported to be 100, 50, 26, 0 in the 1st, 2nd, 3rd, 4th cycle respectively in the batch reaction.